Obtention and characterization of lithium superionic conductors using the glass-ceramic method (2018)
This paper proposes the glass-ceramics method for obtaining lithium ion (Li+) solid electrolytes. This technique provides high chemical and microstructural homogeneity as well as low porosity. Glass samples were subjected to either single or double heat treatments, between 700 °C and 1000 °C, in order to obtain the glass-ceramics. Differential Scanning Calorimetry – DSC – results evidenced the possibility of fabricating these ceramics from glass in the system Li2O·Al2O3·TiO2·P2O5. Samples observed by Scanning Electron Microscopy – SEM – showed a finely grained microstructure which was homogeneously distributed and non-porous. X-ray Diffraction – XRD – patterns showed the formation of the high conducting phase LiTi2(PO4)3. A high ionic conductivity, in the order of 10-3 S/cm at 1000 °C, was measured by Impedance Spectroscopy – IS. It suggests that the synthesis method used in this research is useful for fabricating lithium ion glass-ceramics and opens up a new alternative for manufacturing different electrical ceramics.